Teacher self-efficacy, instructional quality, and student motivational beliefs: An analysis using multilevel structural equation modeling. (April 2020) - Burić, Irena; Kim, Lisa E.
Abstract: Teacher self-efficacy (TSE) is one of the most salient motivational characteristics that is assumed to affect teachers' instructional quality and student motivational beliefs. However, discussions of these associations have primarily been often primarily conceptual and/or based on empirical research that has suffered from methodological shortcomings. Therefore, the aim of this study was to examine the relationships between TSE, instructional quality (i.e., classroom management, cognitive activation, and supportive climate) and student motivational beliefs (i.e., self-efficacy and intrinsic motivation) by using responses from both teachers and students and implementing a sophisticated doubly latent multilevel structural equation modeling approach. A total of 94 high school teachers and their 2087 students participated in the study. The results demonstrated that, at the class level, TSE was positively related to the three dimensions of instructional quality but not to student motivational beliefs. As expected, instructional quality was positively related to student motivational beliefs. Highlights: Teacher self-efficacy (TSE) is positively related to instructional quality. Instructional quality is positively related to student motivational beliefs. No direct association between TSE and student motivational beliefs could be found.